2003
DOI: 10.1046/j.1468-1331.2003.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety disorders associated with headache frequency. The Nord‐Trøndelag Health Study

Abstract: The aim of this large cross-sectional population-based study was to examine the association between migraine, non-migrainous headache and headache frequency with depression, and anxiety disorders. From 1995 to 1997, all 92 566 inhabitants aged 20 years and above in Nord-Trøndelag County in Norway were invited to participate in the Nord-Trøndelag Health Study ('Helseundersøkelsen i Nord-Trøndelag' = HUNT-2). A total of 64 560 participated, whereof 51 383 subjects (80%) completed a headache questionnaire that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
252
10
15

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(306 citation statements)
references
References 35 publications
29
252
10
15
Order By: Relevance
“…Although research showed that headaches are usually part of the anxiety scale (e.g. Al-Turkait et al, 2011; Glaesmer et al, 2013) or at least coincide with depression and anxiety (Juang, Wang, Fuh, Lu, & Su, 2000; Zwart et al, 2003), in our non-western refugee groups headache was part of neither the depression nor the anxiety scale. This indicates that among non-western refugee groups headache is not part of depression or anxiety.…”
Section: Discussioncontrasting
confidence: 53%
“…Although research showed that headaches are usually part of the anxiety scale (e.g. Al-Turkait et al, 2011; Glaesmer et al, 2013) or at least coincide with depression and anxiety (Juang, Wang, Fuh, Lu, & Su, 2000; Zwart et al, 2003), in our non-western refugee groups headache was part of neither the depression nor the anxiety scale. This indicates that among non-western refugee groups headache is not part of depression or anxiety.…”
Section: Discussioncontrasting
confidence: 53%
“…In addition, migraine at baseline increased the risk of developing depression (RR= 5.8;3) [66]. In another cross-sectional study, including over 50 000 adults age 20 and older, migraine headache was positively associated with depression (OR= 2.7; 95% CI 2.3-3.2) and anxiety disorders (OR=3.2; 95% CI 2.8-3.6) [62]. These associations are not specific to migraine, where nonmigraine headache was related with depression (OR=2.2; 95%CI 2.0-2.5) and anxiety disorders (OR=2.7; 95% CI 2.4-3.0) as well.…”
mentioning
confidence: 97%
“…menstruation, ovulation, oral contraceptives), sleep disturbance, weather changes, psychological factors, alcohol and nutrition (e.g. chocolate) are suggested to be risk factors for triggering migraine headaches [58][59][60][61][62][63][64][65][66][67]. More specifically, the risk of occurrence and persistence of headache despite treatment increases with menstruation [61], while hormone replacement therapy appears to contribute to prolongation of migraine headaches into older age [68].…”
mentioning
confidence: 99%
“…In this view a two-way relationship could link the conditions, primary headaches and psychopathology, with a mutual vulnerability between them. Longitudinal studies on patients with headache show that severity of the headache is positively correlated with the risk of developing mood or anxiety disorder [6]. Breslau et al [7] also have shown that women with a higher score on the subscale for neuroticism of the EPQ inventory had a higher risk for migraine after a 5-year follow-up.…”
Section: Claudio Gentili Patrizia Panicucci Mario Guazzellimentioning
confidence: 99%